The Rational-Based Right to Punishment - MEHDI MUSAZADEH KOFI; alihosein najafiabrandabadi; bagher shamloo; firoz mahmodi janaki (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2021)
AbstractThe legitimacy and acceptability of punishment is dependent on the legitimacy of its constructive political structures. To legitimize the political structures, we need the rule of law. Governments acting according to law consider rationality as a measure of legitimacy and credit the values and moral, social, and cultural norms of society. In modern governments based on wisdom, the principle of preserving the natural rights of humans and freedom has been established on reason. Citizens have the right to protest against it when governments fail to do their duty in protecting citizens’ freedoms. The principle of the right of states to punish, the basis and its principled structure and its effects, are the questions of the present study which has been carried out in descriptive-analytic mode. The right of citizens to rehabilitation and justice desert, as well as the rights of citizens to civil disobedience, and the right not to be punished are the results of the application of the rational-based right to punishment. The consequences of rational punishment are the mitigation and humanization of punishment and providing reasonable benefits to victims, criminals, and citizens.